Ex vivo Platforms to Study the Primary and Recall Immune Responses to Intracellular Mycobacterial Pathogens and Peptide-Based Vaccines - Davis, William C.; Mahmoud, Asmaa H.; Abdellrazeq, Gaber S.; Elnaggar, Mahmoud M.; Dahl, John L.; Hulubei, Victoria; Fry, Lindsay M. (Frontiers in Veterinary Science, 2022)
Progress in the study of the immune response to pathogens and candidate vaccines has been impeded by limitations in the methods to study the functional activity of T-cell subsets proliferating in response to antigens processed and presented by antigen presenting cells (APC). As described in this review, during our studies of the bovine immune response to a candidate peptide-based vaccine and candidate rel deletion mutants in Mycobacterium avium paratuberculosis (Map) and Mycbacterium bovis (BCG), we developed methods to study the primary and recall CD4 and CD8 T-cell responses using an ex vivo platform. An assay was developed to study intracellular killing of bacteria mediated by CD8 T cells using quantitative PCR to distinguish live bacteria from dead bacteria in a mixed population of live and dead bacteria. Through use of these assays, we were able to demonstrate vaccination with live rel Map and BCG deletion mutants and a Map peptide-based vaccine elicit development of CD8 cytotoxic T cells with the ability to kill intracellular bacteria using the perforin-granzyme B pathway. We also demonstrated tri-directional signaling between CD4 and CD8 T cells and antigen-primed APC is essential for eliciting CD8 cytotoxic T cells. Herein, we describe development of the assays and review progress made through their use in the study of the immune response to mycobacterial pathogens and candidate vaccines. The methods obviate some of the major difficulties encountered in characterizing the cell-mediated immune response to pathogens and development of attenuated and peptide-based vaccines.